Unsteady analysis of natural convection in a carbon nanotube-water filled cavity with an inclined heater. (2nd April 2016) - Rahman, M. M.; Öztop, H. F.; Joarder, A. H.; Saidur, R.; Hamzah, N.; Al-Salem, K.; Ibrahim, Talaat A.
ABSTRACT: A finite element solution has been performed in this work to solve unsteady governing equations of natural convection in a carbon nanotube–water-filled cavity with inclined heater. The temperature of ceiling and left vertical walls is lower than that of the heater while the other walls are adiabatic. The main governing parameters are nanofluid volume fraction and Rayleigh number ( Ra ). It is found that the heat transfer rate shows different trends based on Rayleigh number and it increases with increase in nanoparticle volume fraction. It has been estimated that average Nusselt number ( Nu ) is dependent on Ra through power regression models with strong positive linear correlation between ln ( Nu ) and ln ( Ra ). In particular, for the maximum time, when the solid volume fraction is varied from 0 to 0.1 the dependence between average Nu and linear Ra, on a logarithmic scale, is very high.